HOW DOES CORPORATE SOCIAL RESPONSIBILITY ENHANCE THE PERFORMANCE OF OIL PALM COMPANIES IN INDONESIA? - Asna Asna; Puspitosari Puspitosari; Arien Anjar (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
For the last few decades, the Indonesian Oil Palm industry has contributed to economic development by reflecting on the percentage contribution to the Gross Domestic Product. However, most of those companies had a history of poor financial performance. Poor performance has been linked to inefficient corporate social responsibility. Thus, this study aimed to examine the relationship between corporate social responsibility and company performance. A quantitative research design approach was chosen, with a questionnaire developed for primary data collection via a survey of 231 Indonesian oil palm companies’ board of directors from three regions using the cluster random sampling technique. The partial least square regression was applied to analyze the relationship between the variables. The findings show that the dimension of corporate social responsibility such as environment responsibility and community responsibility have significant effect on company performance. The findings have various consequences for the company's owner, as well as stakeholder parties, who believe that the company should adopt the main corporate strategy to fulfil the interests of two parties. As a result, it will create positive vibes from those parties, which will result in better company performance. Keywords: company performance, corporate social responsibility, employee responsibility, environment responsibility, community responsibility.